PACIOLI. - Taylor, R. Emmett (The Accounting Review, 1935)
The article focuses on a scholar Lucas Pacioli, who showed such proficiency in his mathematics that he outdistanced his master. Many tutors in those days were treated as ordinary servants, but this could not have been the case with Pacioli because he stayed with them so long and because, at a later time, he dedicated his first book on mathematics to his three former students. All of Pacioli's time in Venice was not devoted to examining the ways of merchants or in tutoring the three young men. There were in the city competent teachers of mathematics under whom Pacioli enrolled. He was busy making friends with some of his classmates who were to be helpful to him later on. Pacioli wanted to get his mathematics into the hands of people. He wanted them to apply mathematics to everyday life. If he wrote in the language of the people he would be sneered at by the learned. He used a combination of the Latin and the Italian of the time. Pacioli was typically of the Renaissance. He knew business, mathematics, teaching, religion, writing, architecture, sculpture, painting, military science, medicine and music. His great aim was to diffuse knowledge and apply it. Such a restless, ambitious, energetic individual breaking loose from the bonds of the medieval ages.